Inclusive Banking In India Re-imagining The Bank Business Model - Kulkarni, Lalitagauri; Joshi, Vasant Chintaman (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2021)
XIX, 195 p. 44 illus., 37 illus. in color.